REVIVE - Vector surveillance network in Portugal - Osório, H.C. (2017)
In this study, we present an overview of the REVIVE program and updated information on the distribution of some important mosquito species. This entomological network assumes extreme importance, since Portugal shares subtantial trade and travel with Brazil and some African countries (Angola, Mozambique, Cape Verde, Guinea-Bissau and São Tomé and Príncipe), with several imported arboviruses viremic cases detected anually. Furthermore, Ae. albopictus circulates in Spain closer to the Portuguese border and Ae. aegypti is establish in Madeira island, where the most recent outbreak of Dengue in Europe was reported.